Psychosocial, Clinical, and Demographic Factors in Antenatal Depression and Anxiety: A Cross-Sectional Study - Parveen Azam, Tashmina Razzaq, Qamoos Razzaq, Zarina Khan, Attaullah, Nazneen Iqbal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Depression and generalized anxiety disorder (GAD) during pregnancy are prevalent and contribute significantly to maternal and fetal health outcomes. Understanding the factors influencing the development of these conditions is crucial for early intervention and management. Objective: To investigate the factors associated with depression and generalized anxiety disorder during the antenatal period in a cohort of 180 pregnant women. Methods: A cross-sectional study was conducted among 180 pregnant women attending an antenatal clinic. Data was collected using standardized tools: the Edinburgh Postnatal Depression Scale (EPDS) for depression and the Generalized Anxiety Disorder-7 (GAD-7) for anxiety. Sociodemographic, clinical, and psychosocial factors were assessed through structured interviews. Logistic regression analysis was employed to identify the factors associated with depression and GAD. Results: The study found a significant association between depression and anxiety with a history of mental health disorders (p < 0.001), low socioeconomic status (p = 0.01), unplanned pregnancy (p = 0.04), and inadequate social support (p = 0.02). Chronic medical conditions (p = 0.03) and pregnancy complications (p = 0.05) were also identified as significant predictors of antenatal depression and anxiety. Conclusion: This study identifies several key factors contributing to antenatal depression and anxiety, including psychosocial, medical, and reproductive factors. Addressing these factors through targeted interventions could improve mental health outcomes for pregnant women. Keywords: Depression, Generalized Anxiety Disorder, Antenatal, Pregnancy, Risk Factors, Mental Health